2014
DOI: 10.1089/omi.2013.0144
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Alcohol Syndrome, Chemo-Biology and OMICS: Ethanol Effects on Vitamin Metabolism During Neurodevelopment as Measured by Systems Biology Analysis

Abstract: Fetal alcohol syndrome (FAS) is a prenatal disease characterized by fetal morphological and neurological abnormalities originating from exposure to alcohol. Although FAS is a well-described pathology, the molecular mechanisms underlying its progression are virtually unknown. Moreover, alcohol abuse can affect vitamin metabolism and absorption, although how alcohol impairs such biochemical pathways remains to be elucidated. We employed a variety of systems chemo-biology tools to understand the interplay between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 66 publications
0
8
1
Order By: Relevance
“…On a final note, two large protein groups (metabolism and structure) identified in cerebral arteries as targets of PAE, are strikingly like data from a global chemo-biology approach used to analyze murine neuronal tissue following PAE (74). This similarity raises the question as to whether PAE exerts universal effect on various tissues/organs.…”
Section: Discussionmentioning
confidence: 89%
“…On a final note, two large protein groups (metabolism and structure) identified in cerebral arteries as targets of PAE, are strikingly like data from a global chemo-biology approach used to analyze murine neuronal tissue following PAE (74). This similarity raises the question as to whether PAE exerts universal effect on various tissues/organs.…”
Section: Discussionmentioning
confidence: 89%
“…Effects on fetal micronutrient levels in the brains of FAE offspring are both more plausible and less amenable to control (Shankar, Ronis, & Badger, 2007; Weinberg, 1984). It is known (review: Feltes, de Faria Poloni, Nunes, & Bonatto, 2014) that ethanol impairs intestinal absorption and metabolism of particular vitamins and other micronutrients and that normally sufficient levels of zinc and iron (Keen et al, 2010; Rufer et al, 2012) may be inadequate for neural development under conditions of maternal ethanol consumption. Of the principal vitamins, folic acid, a micronutrient critical to fetal brain development (Christensen & Rosenblatt, 1995), and nicotinamide (Ieraci & Herrera, 2006) are selectively depleted by chronic ethanol exposure, while conversion of vitamin A to retinoic acid (Keir, 1991; Zachman & Grummer, 1998) is competitively antagonized by ethanol.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation with each of these micronutrients, as well as vitamins C and E, produced modest improvement in either the neural and/or behavioral effects of fetal ethanol exposure (e.g., Hewitt et al, 2011;Ieraci & Herrera, 2006;Marino Aksenov, & Kelly, 2004;Naseer et al, 2011;Wang et al, 2009), but the mechanisms of damage and amelioration have not been persuasively identified. Using a systems approach and transcriptome data, Feltes et al (2014) have shown that genes related to retinoic acid, the niacin component of nicotinamide, and folate metabo-lism were underexpressed in mice exposed to ethanol at 14-16 days of gestation. Another relevant focus of contemporary study is the epigenome: among other effects, ethanol enhances global DNA hypermethylation in frontal cortex and hippocampus (Muralidharan, Sarmah, Zhou, & Marrs, 2013;Zhou et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The important role of CYP2E1 in producing carcinogenic etheno-DNA lesions was consistently reported in the experimental model and alcoholic individuals ). In addition, abnormal retinoic acid metabolism is considered important in fetal alcohol syndrome or effects due to its importance in early development and differentiation (Feltes, de Faria Poloni, Nunes, & Bonatto, 2014;Kane, Folias, Wang, & Napoli, 2010;Keyte & Hutson, 2012).…”
Section: Role and Regulation Of Cyp2e1 In Liver Diseasementioning
confidence: 99%